Análisis de la presencia de escherichia coli blee en el proceso de compostaje del estiércol de Ganado bovino compostado en una Hacienda Lechera en Quito – Ecuador. - Mesa Montalvo, Edwin Fernando (2022)
The misuse of antibiotics has generated a catastrophic global problem, such as antimicrobial resistance (AMR), causing serious problems to the health system, as the drugs used for high priority diseases are providing ineffective, and this is partly attributed to livestock production. 7 plates were cultivated with Agar TBX and 7 with TBX+Ceftriaxone (CRO), where bacterial growth was obtained, leading them to quantification and evidencing countless growth in p1 (mesophilic phase), with 1000000 CFU E. coli/g in TBX, and TBX+CRO obtained 200 CFU E. coli, p2 (Thermophilic Phase) showed low growth with 170 CFU E.coli/g in TBX, and TBX+CRO obtained 0, and in p3 (Maturation or cooling phase) obtained 3350633.3 CFU E.coli/g in TBX and with TBX+CRO 73.3 CFU E.coli/g. In the sensitivity and resistance evaluation, an antibiogram was carried out determining 71.4% sensitivity and 28.6% resistance to Escherichia coli BLEE evaluated with CLSI (Clinical and Laboratory Standards Institute) parameters. Genotyping showed the existence of CTX-M 1, CTX-M 2, and CTX-M-8 genes; therefore, the results of this study show that the presence of E. coli BLEE was obtained in the composting process. The conclusion is that AMR is present, although, in small quantities, it is increasing since resistant bacteria were obtained at all points. The antibiogram showed resistance to 6 antimicrobials out of 21 tested, along with dependent and intermediate sensitivity, while genotyping showed the presence of CTX-M genes.